PENGARUH GAYA KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP MOTIVASI KERJA KARYAWAN PADA PT. GHIM LI INDONESIA - Tamaria Purba,; Riki, (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2021)
This study aims to determine the effect of leadership style, work discipline on work motivation of employees of PT. Ghim Li Indonesia and to determine the effect of leadership style and work discipline together significantly on the work motivation of employees of PT. Ghim Li Indonesia. The population in this study were all employees of PT. Ghim Li Indonesia, data were collected through questionnaires distributed to 62 respondents using random sampling technique. The data analysis technique used is the F test, t test, and determination test. The results of hypothesis testing have proven that there is an influence between leadership style and work motivation. Tests prove that leadership style has a positive effect on work motivation. Judging from the calculations that have been done, the coefficient value is 0.316 and the t-count value is 3.784 with a significance value of 0.000 which is smaller than 0.05, thus Ha is accepted and Ho is rejected. The results of hypothesis testing have proven that there is an influence between work discipline and work motivation. The test proves that work discipline has a positive effect on work motivation. Judging from the calculations that have been made, the coefficient value is 0.222 and the t-count value is 2.665 with a statistical significance level of 0.009 which is smaller than 0.05, which means that the hypothesis in this study rejects Ho and accepts Ha. Testing the effect of independent variables together on the dependent variable was carried out using the F test. The results of statistical calculations showed the calculated F value = 254,719. By using a significance limit of 0.05, it is obtained that the significance value is smaller than 0.05, which is 0.000.